Meningkatkan Keterampilan Proses Sains (KPS) Peserta Didik Menggunakan Model Pembelajaran Problem Based Learning (PBL) pada Kelas X MIPA di SMA Negeri 6 Pontianak - Sri Puji Astuti; Titin Titin; Ruwiyati Ruwiyati; Erniwati Sinaga (FKIP Universitas Khairun, 2025)
This research was undermined by the low level of science process skills of students of class X MIPA in high school state 6 Pontianak. The research aims to know the improvement of the skills of the science process participants learn on the material of the ecosystem. The subjects of this survey are students of class X MIPA State High School 6 Pontianak who have a total of 29 students. This type of research is a collaborative class action study consisting of 4 stages namely action planning, action implementation, observation and reflection. Data collection techniques use non-testing techniques with observation sheets. Research results show that the PBL learning model can improve the learning process science skills of the learners. This is characterized by an increase in student observation results on cycle 1 by 59% and there are cycles II by 82% with an increase of 23%.Ã‚Â An increase in the indicator observed by 16%, formulated hypotheses by 31%, classified by 14%, planned experiments by 24%, implemented concepts by 25%, drawn conclusions by 32%, and communicated by 19%. Based on the results of research, it can be concluded that bringing a problem-based learning model can improve the skills of science process classes X MIPA High School State 6 Pontianak.